Mirrors of justice law and power in the post-Cold War era - Clarke, Kamari Maxine, 1966-; Goodale, Mark (Cambridge University Press, 2010)
"Mirrors of Justice is a groundbreaking study of the meanings of and possibilities for justice in the contemporary world. The book brings together a group of both prominent and emerging scholars to reconsider the relationships between justice, international law, culture, power, and history through case studies of a wide range of justice processes. The book's eighteen authors examine the ambiguities of justice in Europe, Africa, Latin America, Asia, the Middle East, and Melanesia through critical empirical and historical chapters. The introduction makes an important contribution to our understanding of the multiplicity of justice in the twenty-first century by providing an interdisciplinary theoretical framework that synthesizes the book's chapters with leading-edge literatures on human rights, legal pluralism, and international law"--Provided by publisher.